Site-specific cleavage of left-handed DNA in pBR322 by lambda-tris(diphenylphenanthroline)cobalt(III). - Barton, J K (1985)
The chiral complex tris(4,7-diphenyl-1,10-phenanthroline)cobalt(III), lambda-Co(DiP)3(3+), binds to and, with photoactivation, cleaves left-handed DNA helices, thereby providing a unique molecular probe for local DNA conformation. We have mapped the specific left-handed sites where lambda-Co(DiP)3(3+) cleaves in the plasmids pBR322 and pLP32, which is the derivative of pBR322 containing a Z-form d(C-G)16 insert. For pLP32, a primary cleavage is at the insert; for native pBR322, cleavage occurs at four discrete sites: 1.45, 2.3, 3.3, and 4.2 kilobase pairs. These sites correspond to segments of alternating purine-pyrimidines. Moreover, these positions map to the ends of the three distinct coding regions in pBR322: the tetracycline-resistance gene, the origin of replication, and either end of the ampicillin-resistance (beta-lactamase) gene. The locations of these left-handed segments suggest to us that Z-DNA might serve as a conformational punctuation mark to demarcate the ends of genes.